A model undergraduate university curriculum in technology management. (1st January 1999) - Hauck, Allan J.
A model undergraduate curriculum in technology management, which also uses the tools associated with productivity and quality improvement, recently has been implemented at Colorado State University and is described here. This curriculum was developed around a core of introductory courses and served as a means of integrating existing programs in Construction Management, Industrial Technology Management, and Technology Education and Training. To this core of foundational skills, each of the three majors structured an array of upper division coursework in engineering science, general business, technology processes, and the management and educational practices specific to the demands of each discipline. The outcome of this reform effort was recognition of a common theoretical framework, which linked these university disciplines to each other as well as to technology management trends in the industries they serve.